The economic costs of seal presence in Swedish small-scale fisheries. (26th November 2019) - Waldo, Staffan; Paulrud, Anton; Blomquist, Johan
Abstract: Growing seal populations are examples of successful marine management, and the seals are often seen as a symbol of a thriving ecosystem. However, seals are well known to interact with local small-scale fisheries by feeding from the gears. This causes both lost catches and broken gear, which negatively affect the economic viability of the small-scale fisheries. While lost catches are known to be substantial, no information is currently available on costs for mending gear, searching for fishing grounds with less seals, etc. This article estimates these costs from a questionnaire sent to Swedish fishers. The total cost due to seals for small-scale fisheries is about €690 000, which corresponds to 7% of the expenditure for purchased goods (not labour and capital). The total time spent on seal-related work corresponds to ∼8% of total working time. Combining additional costs with revenue losses due to decreased catches, it is shown that the economic viability of the small-scale fisheries becomes low due to the seal interaction, which affects the economic and social sustainability of the sector.